(untitled) (American Journal of Research in Humanities and Social Sciences, 2025)
One of the most urgent tasks is to improve the lives of rural residents, whose role and importance in the development of the country are incomparable, to a level that meets modern standards. For this, housing construction, the provision of communal services and improving household services are of great importance in the socio-economic development of villages. The main part of the republican and local budgets was allocated for housing construction and improving communal services.